2019
DOI: 10.1002/jsfa.10138
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of emulsion gels formulated with chestnut (Castanea sativa M.) flour and chia (Salvia hispanica L) oil as partial fat replacers in pork burger formulation

Abstract: BACKGROUND: The aim of this work was to evaluate the effect on chemical composition, physico-chemical properties, cooking characteristics, fatty acid profile, lipid oxidation, and sensory acceptability of an oil-in-water emulsion gel that was prepared with chestnut flour, chia oil, gellan gum, and water (CEG), used as a fat replacer in pork burgers. The original mixture was used as a control sample (CS). The other samples were formulated partially replacing pork backfat with 5% of CEG (CEG5%) and 10% of CEG (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 40 publications
9
31
0
Order By: Relevance
“…In contrast, a * remained constant, indicating that the fat substitution was not significant on this index. Moreover, in a previous study, the fat substitution with a chia oil emulsion gel caused no significant variations of a * but significant changes of L * and b * [ 49 ]. In the same study, L * and b * were slightly higher than ours, probably because of the presence of the oil in the fat replacer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a * remained constant, indicating that the fat substitution was not significant on this index. Moreover, in a previous study, the fat substitution with a chia oil emulsion gel caused no significant variations of a * but significant changes of L * and b * [ 49 ]. In the same study, L * and b * were slightly higher than ours, probably because of the presence of the oil in the fat replacer.…”
Section: Resultsmentioning
confidence: 99%
“…The color of burgers reformulated with fat replacers is influenced by the type of ingredients used for this purpose. In particular, Lucas-González et al [ 49 ] reported a decrease of L * and an increase of a * during cooking of burgers formulated with chestnut flour and chia oil emulsion gels. By contrast, Heck et al [ 43 ] reported an increase of L * and a decrease of a * in cooked burgers produced by the inclusion of linseed or chia oil microparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The principal problems to the direct incorporation of this oil into meat products are the technological difficulty for their integration in the meat batter, the instability to oxidation (due to the high of unsaturation of fatty acids), and their negative effects on sensorial attributes. To prevent this, several strategies have been developed like microencapsulation with rosemary antioxidants (burgers [ 104 ]), conventional oil-in-water emulsions (cooked lamb sausages [ 107 ] and frankfurter [ 102 ]), double emulsions (meat systems [ 123 ]), emulsion gels (burgers [ 105 ]; bolognas [ 117 ]; and fresh sausages [ 112 ]) or hydrogel emulsions (low-fat burgers [ 106 ] and lamb sausages [ 113 ]). These methodologies allow the chia oil able to be stabilized or immobilized in the protein matrix, reducing the chances of bulk oil physically separating from the structure of the meat product, and so remaining stable during processing and storage.…”
Section: Oxidation Stability Of Meat Products Containing Chia Quimentioning
confidence: 99%
“…Similar study has been reported by McClements et al [617] Paunov et al [618] reported the use of a temperature insensitive, food-grade, mixed agarmethylcellulose hydrogel to reduce the caloric density of pancakes that were prepared at temperatures much higher than the boiling point of water. McClements et al [617,[619][620][621][622] reported that the application of emulsion hydrogels in reduced-fat food, by replacing animal oils with vegetable oils. [616] In food engineering and processing field Food packaging materials Hydrogel as food packaging material is an important solution to the increasingly serious issue that abundant use and misuse of large molecular weight petroleum-based polymeric materials.…”
Section: Calorie Controlmentioning
confidence: 99%